STOK KARBON DI ATAS PERMUKAAN TANAH PADA HUTAN MANGROVE SUNGAI AWAN KIRI KABUPATEN KETAPANG - Kusmawati, Kusmawati; Hardiansyah, Gusti; Widhanarto, Ganjar Oki (JURNAL HUTAN LESTARI, 2021)
Mangrove forests, often referred to as mangrove forests, brackish forests or tidal forests, is a transitional ecosystem between land and sea which are tropical or sub-tropical areas along the sheltered coast and river mouth. Mangrove forest is a coastal plant community dominated by several species of mangrove trees that are able to grow and develop during the tides in accordance with their tolerance to salinity, duration of inundation, substrate and beach morphology. Awan Kiri Mangrove Forest has a total area of 114 hectares including the area of Other Management Areas (APL) then seen from the density of the Mangrove Forest only has 92 hectares. This study uses a non-destructive survey method. Vegetation carbon stock calculation is carried out using vegetation biomass calculation approach. Vegetation biomass calculation based on the calculation of allometric equations. Calculation the value of stored carbon using the formula according to (SNI 7724:2011) the value of parent carbon content,amounting to 0,47. Bassed on the research that has been done, it is found that there are 185 individuals, Rhizophora spp., Bruguiera gymnorhiza, Rhizpphora apiculata, Xylocarpus gerantum and Excoecaria agallocha. The biomassa content can be known in the 3 pathways to store 242,16 tons biomassa and the totalÂ  biomassa content in 1210,8 tons/ha with an everage of 403,6 tons/ha. The carbon content is 569,06 tons/ha so that it gets an average total of 186,68 tons C/ha.Keywords: Carbon Stock, Ketapang Regency, Sungai Awan Kiri in Mangrove Forests.